Engineering a polyoxometalate-based metal organic framework with more exposed active edge sites of Ag for visible light-driven selective oxidation of cis-cyclooctene. Issue 10 (30th August 2018) - Lin, Xiaoling; Zhang, Mengling; Zhu, Mengmeng; Huang, Hui; Shi, Chunfeng; Liu, Yang; Kang, Zhenhui
Abstract : The polyoxometalate-based MOF with exposed active edge sites of Ag was designed for visible light-driven selective oxidation of cis -cyclooctene. Abstract : Epoxides are an extremely important class of chemical intermediates in the chemical industry due to the versatility of epoxides in preparing many fine and specialty chemicals. However, designing more active and selective heterogeneous catalysts in epoxidation is still a priority and a challenge. In this work, we demonstrate the synthesis of two new Ag/polyoxometalate-based coordination polymers (Ag8 (mttz)4 (H2 O)[PW V WVI11O40 ]·H2 O (1 ) and Ag8 (mttz)4 (H2 O)[PMo V MoVI11O40 ] (2 ), mttz = 5-methylthio-2 H -tetrazole) that are highly active for the selective oxidation of cis -cyclooctene to epoxycyclooctane under mild conditions (solvent-free, atmospheric pressure, 70 °C with H2 O2 as the oxidant under visible light). It is worth noting that compound1 possesses abundant exposed active edge sites of Ag, resulting in the catalytic performance achieved in the selective oxidation of cis -cyclooctene to epoxycyclooctane being superior to its components (metal, polyoxometalates and ligand) and compound2 with the conversion/selectivity to epoxycyclooctane of 70.15/99.68%, respectively. The excellent photocatalytic activity of compound1 should be attributed to the synergy of the components after coordination polymerization and its structure with exposed active edge sites of Ag.